Effect of hapa size on conditioning of broodstock Oreochromis niloticus in fertilized earthen ponds - Ambali, Aggrey J. D.; Little, David C.; Machintosh, Donald J.; Yakupitiyage, Amararatne; ICLARM\GTZ (Bangkok : Asian Institute of Technology, 1990)
The study was carried out to determine the effect of manipulating hapa size during conditioning period of female Oreochromis niloticus brood stock in fertilized earthen pond on seed production. An equal biomass of female brood fish was stocked during conditioning in each of three different sized hapas, a) 2. 72m2(High density) b) 5.29m2(Medium density) and c ) 10.78m2(Low density). The stocked biomass\m2 was 0.Gkg ; 1.2-1 . 4kg and 2 . 3-2 . 5kg for low, medium and high stocking density respectively. After a period of 10 day conditioning, females were stocked in 40m~ hapas at a stocking ratio of 1:1 and allowed to spawn naturally over a period of 5 days. No significant difference in seed yield were recorded, treatments exceeded 3000 seed\kg female spawned per month 40x10 per total ha pond area. but and There was a positive response to the use of conditioned males for 5 days prior to spawning on seed production. Females stocked with conditioned males produced seed exceeding 8200 per kg females spawned while those stocked with unconditioned males produced less than 8200 seed per kg female spawned . The mean clutch size was significantly(p<0 . 05) higher in the low density treatments compared to the other two treatments 1042, 804 and 839 seed\female for low, medium a nd high densities respectively. However relative clutch size was not significantly different(p>0.05) among the three treatments 9, 9, 8 seed\g female for low, medium and high density treatments . Water quality deteriorated during day 45 to 60 of the experimental period when dissolved oxygen concentration was lower than 0.5mg\l in the conditioning heparin the morning. Decline in water quality coincided with drop in seed production .
A thesis submitted in partial fulfillment requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1990
Keywords: Tilapia; Fishes -- Reproduction